The Potential of Cryptophyte Algae in Biomedical and Pharmaceutical Applications - Abidizadegan, Maryam; Peltomaa, Elina; Blomster, Jaanika (Frontiers in Pharmacology, 2021)
Microalgae produce a variety of bioactive components that provide benefits to human and animal health. Cryptophytes are one of the major groups of microalgae, with more than 20 genera comprised of 200 species. Recently, cryptophytes have attracted scientific attention because of their characteristics and biotechnological potential. For example, they are rich in a number of chemical compounds, such as fatty acids, carotenoids, phycobiliproteins and polysaccharides, which are mainly used for food, medicine, cosmetics and pharmaceuticals. This paper provides a review of studies that assess protective algal compounds and introduce cryptophytes as a remarkable source of bioactive components that may be usable in biomedical and pharmaceutical sciences.